Carbon Footprint of Indonesia’s Tropical Forests: Between Conservation, Commodity, and Climate Crisis - Manek, Luisa M. (Journal of Horizon, 2025)
Indonesia’s tropical forests play a central role in the global climate system because they act as significant carbon sinks while also possessing the potential to become major sources of emissions under deforestation pressure. This study examines the complex relationship between conservation policy, commodity-driven land expansion, and the climate crisis in shaping the carbon footprint of Indonesia’s forests. A qualitative systematic review approach was used to synthesize academic publications from the last decade, focusing on forest carbon dynamics, governance mechanisms, and environmental policy. Findings show that conservation strategies grounded in ecosystem services, community participation, and integrated terrestrial and coastal management offer long-term mitigation potential, whereas commodity-based economic growth models intensify carbon emissions and undermine climate pledges. The study demonstrates that technological solutions alone cannot substitute structural governance reforms, especially when land tenure and benefit-sharing remain unclear. The conclusion emphasizes that climate resilience and sustainable carbon sequestration can be realized only when forest conservation is embedded into national development models that reduce reliance on extractive industries and ensure equitable socio-institutional participation. The research contributes novelty by integrating conservation, commodity, and climate governance dimensions to evaluate whether Indonesia’s tropical forests will remain net carbon sinks or shift into permanent carbon sources